MENINGKATKAN KETERAMPILAN MENULIS TEKS CERITA PENDEK DENGAN MODEL DISCOVERY LEARNING BERBANTUAN CANVA - Siti Mariam Mariam; Aditya Permana; Suhud Aryana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the use of the Canva-assisted discovery learning model. This type of research uses experiments. The researcher found several problems, including the lack of students' interest in writing short story texts, students' difficulties in developing ideas and ideas. This study aims to find out more about improving learning to write short story texts for class IX students using the Canva-assisted discovery learning model. This research method uses a quantitative descriptive method. Subjects in this study used data in the form of tests. The results of the preliminary test (pretest) and the final test (posttest) were used as data acquisition techniques. The results showed that the students' ability to write short story texts on average before using the Canva-assisted discovery learning model. initial (pretest) of 60.03 and after using the discovery learning model assisted by Canva obtained an average value of the final test (posttest) of 84.80. The results of the ability to write short story texts increased by 28%. In conclusion, the use of the Canva-assisted discovery learning model for learning to write short story texts can improve student learning outcomes.